The Politik Uang dalam Sistem Politik Demokratis : Studi Kasus Korea Selatan dan Negara-Negara Eropa - Fauzan Hidayat (Ministry of Home Affairs, 2024)
The issue of money politics in Indonesia has severely undermined democratic integrity, affecting equality in political participation, increasing the risk of corruption, creating disparities in political access, influencing public policy-making, and damaging public perceptions of the political system’s credibility. This study aimed to explore how other countries address the challenges of money politics and offered concrete solutions to strengthen democratic integrity. Using a comparative approach, the study examined money politics policies and practices, as well as assessed the effectiveness of anti-corruption and transparency measures in South Korea and Europe. The findings revealed that strict regulations on campaign financing and oversight by independent bodies have effectively mitigated money politics practices in these countries. Consequently, Indonesia is encouraged to adopt a similar approach by establishing an independent oversight body and fostering active public participation to address the challenges of money politics and high political costs, promote equitable political participation, and strengthen democratic integrity.